Analisis Tingkat Kesejahteraan Keluarga Nelayan (Studi Kasus di Kelompok Nelayan “Tapang Kembar” Kelurahan Sanur, Kecamatan Denpasar Selatan) - SIWI, AVENTIA SELANIKA RIFANI; ANTARA, MADE; ANGGRENI, I.G.A.A LIES (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2023)
Analysis Welfare Level of Fishermen’s Families (Case Studies in the Fishing Group “Tapang Kembar” Sanur Village, South Denpasar District) Sanur is a popular local and international tourist destination with numerous small store and restaurants selling seafood. However, due to visiting limitations imposed during the pandemic, people's purchasing ability for catches and tourist attractions has been limited. This has a negative influence on the livelihoods of people, particularly the